CONTENTS OF ACTIVITIES IN ORGANIZING EDUCATIONAL LESSONS IN OTML (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the organization of training sessions, the use of information technologies, information processes, pedagogical technologies, teaching methods, the contents of training sessions are mentioned.